Comunidade Quilombola Água Limpa, em Faina-GO : as folias de Santos Reis e São João Batista como fortalecimento sociocultural e (re)existência - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
The slavery period accommodated the enslaved blacks in the central breeding place of the colonial system of exploitation. As reactions to the condition of slaves, revolts and the formation of quilombola communities began, which originated, mostly, in two ways: from the flight of individual slaves or in groups, and the purchase of land by free blacks. The research has great relevance when examining the organization of the Quilombola Água Limpa Community, in the municipality of Faina-GO, as a social group, for the cultural identity, tradition and secular customs of the quilombolas in the maintenance and preservation of the peasant way of life, of the knowledge and practices about the Cerrado, of the rituals of the Whoopees (when groups of costumed merry-makers dance through farm) of Saint John Baptist and The Three Wise Men preserved. The objective of this research was to understand the quilombola identity and the relations of religion and religiosity in the maintenance of the territory, from the preservation of the traditions of the Whoopees from The Three Wise Men and Saint John Baptist, in the Quilombola Água Limpa Community, as strategies of permanence in and of the territory. The information and contents collected were possible thanks to bibliographic surveys and readings to understand the relations and concepts of Traditional Communities, Quilombola Community, Territorialization, Deterritorialization, Reterritorialization and Traditional Cultural Manifestations. In the field visits, interviews and observations were conducted, in order to understand the dynamics of the Whoopees and the community, photographic documentation, videos and audios, and a map was also used to locate the study area. Due to the tensions imposed by agribusiness and the lack of public policies that are their right, between the 1990s and 2010, there was an intense process of desterritorialization of families of the community and reterritorialization in urban areas of neighboring municipalities, mostly in the city of Goiás. However, it was established as a strategy of resistance and permanence in the field to faith in the saints, especially Saint John Baptist and in the The Three Wise Men, patrons of that community, a factor that causes the residents to continue to organize the churches every year, tradition that drags on for generations and enables the maintenance of the faith among the residents of the community and those who live in neighboring municipalities.
Keywords: Comunidade Quilombola Água Limpa; Desterritorialização; Reterritorialização; Folia de São João Batista; Folia de Santos Reis; Quilombola Community Água Limpa; Deterritorialization; Reterritorialization; Saint John Baptist Whoopees; The Three Wise Men Whoopees; CIENCIAS HUMANAS::GEOGRAFIA